Evaluation of altered passive eruption in maxillary anterior teeth - Nguyen, Thi Hong; Ho, Xuan Anh Ngoc; Tran, Thien Man; Nguyen, Duc Quynh Trang; Nguyen, Thi Phuong Thao (Tạp chí Y Dược Huế, 2024)
Background: Altered passive eruption (APE) is a condition in which the g does not move in the direction of the apex during teething, making the crown appear shorter and square, changing width/length ratio of clinical crown and the shape of gingival margin. The study evaluated morphological characteristics of maxillary anterior teeth with APE. Materials and Methods: A cross-sectional study was conducted with 30 patients, involving 141 maxillary anterior teeth diagnosed with APE. Results: The widths of crown are: 7.98 mm, 6.43 mm, and 7.48 mm; the lengths of clinical crown are: 7.98 mm, 6.43 mm, and 7.48 mm, and the lengths of anatomical crown are: 10.09 mm, 8.72 mm, and 9.42 mm in the central incisors, lateral incisors, and canines, respectively. The widths of free gingiva recorded in the central incisors: 3.9 mm, lateral incisors: 3.57 mm, and canines: 3.76 mm. The width of keratinized gingiva in the central incisors, lateral incisors, and canines are 7.53 mm, 7.45 mm, and 7.32 mm, respectively. Conclusion: These morphological features assist clinicians in obtaining a broad understanding of the anatomy related to APE, while also aiding in the precise diagnosis and treatment of individual patients.